On the fate of the Irminger Current water and its impact on the convection region in the Irminger Sea – a Lagrangian model study - Nora Fried; Renske Gelderloos; Oliver J. Tooth; Caroline A. Katsman; M. Femke de Jong (Ocean Science, 2026)
The Irminger Sea is one of the few places in the North Atlantic where dense water masses are formed through deep convection. In addition to atmospheric forcing, wintertime convection in the Irminger Sea interior can be impacted by the extent of restratification in the preceding years. In the Irminger Sea, the cold central basin is contrasted to the Irminger Current (IC) which carries warm and saline waters of subtropical origin. In this study, we investigate the potential impact of the IC on restratification of the Irminger Sea's deep convection area (DCA), using one-year output of a high-resolution regional model combined with Lagrangian particle tracking. We release particles over the upper 1500 m of the IC in the eastern Irminger Sea and track them forward-in-time for six months. Of those particles, 39 % follow the boundary current circulation and 60 % enter the interior Irminger Sea. Around 1 % leaves the Irminger Sea through Denmark Strait and across the ridge to the Iceland Basin. From all particles released, about 26 % reach the DCA, steered by mesoscale variability. In this model simulation, the majority of those particles (95 %) enter the DCA in the upper 1500 m of the water column. On their way to the DCA, the IC waters cool and freshen but on average remain lighter than waters in the DCA and therefore have the potential to restratify the DCA. This westward spread of light IC waters constrains the extent of the DCA to the western Irminger Sea by enhancing the stratification in the eastern part of the basin.